Designing and delivering online professional development courses for online educators: lessons from the iEARN online professional development courses - Chitanana, Lockias (IGI Global publication, 2019)
This chapter is based on a study that examined the International Education and Resource Network Science Technology and Math (iEARN-STM) online professional development course. The study used the constructivist framework as the conceptual model to examine the way in which the constructivist theory has shaped the design and implementation of the course, as reflected by the interactions among the participants in the course. The participants were 28 educators, who were working in different educational institutions in different countries throughout the world. The purpose of the study was to identify the constructivist learning principles that were behind the success of the course. The results of the study show that the constructivist approach to course design and delivery provides a powerful structure for creating learning environments conducive to the development of professional skills among educators. The results provide online professional development course designers with insights on how to plan and deliver a successful course.